ANALISIS DINAMIK PADA GEDUNG A1 PEMONDOKAN UPT. ASRAMA HAJI EMBARKASI ACEH DENGAN MENGGUNAKAN METODE TIME HISTORY - Alif Akbar Azani; Aulia Rahman; Munirul Hady; Bunyamin . (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2022)
Indonesia is one of the countries most prone to earthquakes, causing a lot of damage to building structures. Therefore, buildings require earthquake resistance to allow time for building occupants to evacuate from the building. The object of this research is the A1 Hajj Boarding Boarding Building for the Embarkation of Aceh which is located on Teuku Nyak Arif Street, Kuta Alam District. The purpose of this study was to see whether the building met the requirements of SNI 1726-2019 in response to the Simeulue I earthquake with a magnitude of 8.3 on April 11, 2012, using Time History analysis with the help of software ETABS. By reviewing the building deformation, displacement and deviation between levels, knowing the working forces in the form of axial forces, bending moments, and shear forces on the columns and beams of the building. Data processing will be analyzed with the standard rules of SNI 1726-2019. From the analysis, it is found that the basic shear strength due to earthquake loads is 2302.1 kN for the x direction and 637.6 kN for the y direction. The largest maximum lateral displacement is 11.445 mm for the x-direction and 11.774 mm for the y-direction, causing the interstory drift of each combination of loading structures to remain within the limits permitted by earthquake-resistant building standards (SNI 1726:2019). It can be concluded that the Aceh Embarkation Hajj Dormitory Building A1 has been designed in accordance with the SNI 1726:2019 standard.